Epigenetics & Chromatin - Jeltsch, Albert; Henikoff, Steve; Grosveld, Frank; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Epigenetics & Chromatin is a peer-reviewed, open access journal that publishes research, and reviews, providing novel mechanistic insights into epigenetic inheritance and chromatin-based interactions. The journal aims to understand how gene and chromosomal elements are regulated and their activities maintained during processes such as cell division, differentiation and environmental alteration. This encompasses but is not limited to studies addressing: Molecular processes and mechanisms, including histone modifications, DNA methylation and modification, structure and mechanism of epigenetic enzymes, regulation of gene expression, histone variants, linker histones. Chromatin structure and dynamics, including structural and modelling studies, chromatin remodeling, nucleosome positioning, structure and mechanism of chromatin related enzymes and complexes, mechanisms of chromatin regulation, higher order chromatin structure. Epigenetic processes, including genomic imprinting, dosis compensation and X-chromosome inactivation, mitotic & meiotic heritability of epigenetic information. Development of new biochemical and computational tools and methods, including single cell epigenomics approaches, novel epigenome analysis methods, bioinformatic technologies in epigenomics research, epigenome editing, computational epigenomics. Biological processes, including developmental epigenetics, cancer epigenetics, neuroepigenetics, non-coding RNA with roles in epigenetics and chromatin biology, plant epigenetics, epigenetics and metabolism, epigenetics and evolution.
Keywords: Genetics; Medical genetics; Plant genetics; Cytology; Molecular genetics; Genetics and Genomics; Medical Genetics; Plant Genetics; Cell Biology; Molecular Genetics